TENDENCIES AND DIRECTIONS OF DEVELOPMENT OF COOPERATIVE LAW AND COOPERATIVES IN POLAND, ESPECIALLY AGRICULTURAL AND FOOD, HOUSING AND BANK COOPERATIVES - Suchoń, Aneta (International Journal of Cooperative Law, 2023)
Cooperatives are important entities in the economic, social and cultural spheres in Poland. They are of a diversified nature -from large dairy cooperatives, through medium-sized cooperative banks, or housing cooperatives, to small social cooperatives. In Poland, there are currently over 9,500 cooperatives2. There is a large number of housing cooperatives in urban areas. In total, Poland is home to over 3,722 such entities. There is also a large number of cooperatives operating in rural areas and agriculture. However, it is not just the cooperatives established by agricultural producers that are popular –there are also considerable numbers of cooperative banks and ‘Samopomoc Chłopska’ (farmer’s self-help) cooperatives. In turn, ‘Społem’ food cooperatives are popular in many cities, including Warsaw, Kraków and Poznań. It is also worth noting the development of social cooperatives, which are part of the social economy.